Population pharmacokinetic-pharmacodynamic modeling of PB2452, a monoclonal antibody fragment being developed as a ticagrelor reversal agent, in healthy volunteers - Steven J. Kathman; Jeffery J. Wheeler; Deepak L. Bhatt; Susan E. Arnold; John S. Lee (Wiley, 2022)
Abstract PB2452, a neutralizing monoclonal antibody fragment that binds the antiplatelet drug ticagrelor with high affinity, is being developed as a ticagrelor reversal agent. To identify a clinically useful intravenous (i.v.) reversal regimen, a semimechanistic exposure‐response model was developed during the PB2452 first‐in‐human phase I study. From a randomized, double‐blind, placebo‐controlled, single‐dose trial to evaluate the safety, efficacy, and pharmacokinetics (PKs) of PB2452 in 61 healthy volunteers pretreated with ticagrelor, sequential dose cohort data were used to build and refine an exposure‐response model that combined population PK models for ticagrelor (TICA), ticagrelor active metabolite (TAM), and PB2452, and related their binding relationships to the PK of uncomplexed TICA and TAM which is predictive of platelet inhibition. Platelet function was assessed by multiple assays. The model was developed using Bayesian methods in NONMEM. Human PK and pharmacodynamic data from sequential dose cohorts were used to initially define and then refine model parameters. Model simulations indicated that an initial i.v. bolus of PB2452, followed by a high‐rate infusion, and then a slower‐rate infusion would provide immediate and sustained reversal of the antiplatelet effects of ticagrelor. Based on model predictions, a 6 g i.v. bolus followed by 6 g infused over 4 h and then 6 g over 12 h was identified and tested in study subjects and shown to provide complete reversal within 5 min of infusion onset that was sustained for 20-24 h. The model is predictive of the reversal profile of PB2452 and will inform future trials of PB2452.